Decellularized human dermal extracellular matrix-derived scaffolds: compositional, mechanical, and in vitro biological characterizations - Fernández-Carro, Estibaliz; Garcia-Barrios, Alberto; Remacha Gayán, Ana Rosa; Alcaine , Clara; Ciriza Astrain, Jesús (Jornada de Jóvenes Investigadores del I3A, 2023)
Currently, there is a growing demand for in vitro skin models. In search of a more realistic approximation of the tissue microenvironment, here, we present an optimized protocol for extracting and characterizing hydrogels obtained from decellularized dermal extracellular matrix from human skin to generate scaffolds for subsequent use in 3D skin models.